Słoweńskie wybory literatury polskiej: przekłady z lat 1990—2006 / Slovene choices from Polish literature: translations from 1990—2006 - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2009)
Between the years 1990 and 2006, about 50 Polish books (poetry, prose and drama) were translated in already independent Slovenia, also a lot of single poems, short stories and fragments of more substantial compositions. Slovene macrochoices from Polish literature on the one hand constitute continuation of the traditional presence in the Slovene culture, on the other hand they result from increasing language and encyclopedic competencies of the translators. The choices are defined by four criteria: Polishness, empathy, the desire to get to know the Polish mentality, the historically-literal process and personal motivation. The authors of choices and translations of Polish literature are translators belonging to many generations, differently evaluating the needs of a Slovene reader and the character of Polish literature and mentality. Although Polish literature is distinctly present in the Slovene literary life, in the Slovene choices from it dominates perspective of strangeness, with which translators from different generations familiarise the native recepient, choosing works belonging to the canon and often to the opposite pole.